Polymorphism in the Tyrosine Hydroxylase (TH) Gene Is Associated with Activity-Impulsivity in German Shepherd Dogs - Kubinyi, Enikő; Vas, Judit; Hejjas, Krisztina; Ronai, Zsolt; Brúder, Ildikó; Turcsán, Borbála; Sasvari-Szekely, Maria; Miklósi, Ádám (PLOS ONE, 2012)
We investigated the association between repeat polymorphism in intron 4 of the tyrosine hydroxylase (TH) gene and two personality traits, activity-impulsivity and inattention, in German Shepherd Dogs. The behaviour of 104 dogs was characterized by two instruments: (1) the previously validated Dog-Attention Deficit Hyperactivity Disorder Rating Scale (Dog-ADHD RS) filled in by the dog owners and (2) the newly developed Activity-impulsivity Behavioural Scale (AIBS) containing four subtests, scored by the experimenters. Internal consistency, inter-observer reliability, test-retest reliability and convergent validity were demonstrated for AIBS. Dogs possessing at least one short allele were proved to be more active-impulsive by both instruments, compared to dogs carrying two copies of the long allele (activity-impulsivity scale of Dog-ADHD RS: p = 0.007; AIBS: p = 0.023). The results have some potential to support human studies; however, further research should reveal the molecular function of the TH gene variants, and look for the effect in more breeds.